ACE2 and ACE in acute and chronic rejection after human heart transplantation. (15th January 2019) - Soler, Maria Jose; Batlle, Montserrat; Riera, Marta; Campos, Begoña; Ortiz-Perez, José Tomás; Anguiano, Lidia; Roca-Ho, Heleia; Farrero, Marta; Mont, Lluis; Pascual, Julio; Perez-Villa, Felix
Abstract: Objectives: The authors sought to evaluate cardiac activity of angiotensin-converting enzyme (ACE) and ACE2 after heart transplantation (HT) and its relation with acute rejection (AR) and chronic allograft vasculopathy (CAV). Background: The renin-angiotensin system is altered in heart failure and HT. However, ACE and ACE2 activities in post-HT acute and chronic rejection have not been previously studied. Methods: HT patients ( n = 45) were included when appropriate serial endomyocardial biopsies (EMB) and coronary angiography were available for analysis. In 21 patients, three post-HT time points were selected for CAV study in EMB tissue: basal (0–3 wks), second (2–3 months) and third (4–5 months). At 10 years post-HT, CAV was evaluated by coronary angiography (CA) and patients were grouped by degree of CAV: 0–1, non-CAV ( n = 15) and 2–3, CAV ( n = 6). For the AR study, 28 HT patients with evidence of one EMB rejection at grade 3 and two EMB grade 1A and/or 1B rejections were selected. Results: Post-HT, ACE2 activity was increased in the CAV group, compared to non-CAV. Patients with AR showed increased ACE, but not ACE2, activity. Conclusions: Our results suggest that early post-HT cardiac ACE2 activity may have an important role in CAV development. In contrast, ACE activity was increased in AR. The renin-angiotensin system seems to be altered after HT and strategies to balance the system may be useful. Highlights: ACE2 and ACE enzymes are expressed in endomyocardial biopsies after heart transplantation. ACE2 activity is increased in endomyocardial biopsies from patients with crhonic allograft vasculopathy. ACE activity is increased in endomyocardial biopsies form patients with acute heart rejection. Strategies to balance the renin-angiotensin system after heart transplantation may be useful in these patients.